Analysis Of The Effect Of Tax Revenue On Economic Growth In Indonesia - Wibowo, Hendy; Toto Gunarto; Marselina (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Taxes play an important role as one of the main sources of income for the country. The main objective of state financial policy in the field of domestic revenue is to explore, encourage and develop sources of revenue from within the country so that the amount increases in line with development needs. This research uses a quantitative descriptive research type. The data used is in the form of a Time Series (time series) spanning 33 years, with a research time range of 1990-2022, with the Indonesian observation area. The research method uses the OLS (Ordinary Least Square) least squares method and the Error Correction Model. Error Correction Model (ECM). Research Results Income Tax Revenue (PPH) has a positive and significant influence on the long-term relationship with gross domestic product (GDP), and has a positive and significant influence on the short-term relationship. Value added tax (VAT) has a positive and significant influence on the long-term relationship with gross domestic product (GDP), and has a positive and significant influence on the short-term relationship. Excise revenue (PC) has a positive and significant influence on the long-term relationship with gross domestic product (GDP), and has a positive and significant influence on the short-term relationship. Import duty receipts (PBE) have a positive and significant influence on the long-term relationship with gross domestic product (GDP), and have no influence on the short-term relationship in Indonesia throughout the 1990-2022 period.